Challenges in Maintaining the Hemostatic Balance in Children Undergoing Extracorporeal Membrane Oxygenation: A Systematic Literature Review - Drop, Joppe G. F.; Wildschut, Enno D.; Gunput, Sabrina T. G.; de Hoog, Matthijs; van Ommen, C. Heleen (Frontiers in Pediatrics, 2020)
Background: Despite advances in technology and clinical experience, the incidence of hemostatic complications, including bleeding and thrombosis, remains high in children supported with extracorporeal membrane oxygenation (ECMO). These hemostatic complications are important to prevent, since they are associated with increased morbidity and mortality. This systematic literature review aims to outline the most important risk factors for hemostatic complications in children undergoing ECMO treatment, to summarize the reported alternative anticoagulant drugs used in pediatric ECMO and to describe studied associations between coagulation tests and hemostatic complications. Methods: A literature search was performed in Embase, Medline, Web of Science Core Collection, Cochrane Central Register of Controlled Trials, and Google Scholar in February 2020. Included studies were studies evaluating children (<18 years old) treated with ECMO, and studies evaluating risk factors for hemostatic complications, alternative anticoagulants, or the association between coagulation tests and hemostatic complications. Results: Out of 1152 articles, 35 studies were included. Thirteen out of 49 risk factors were investigated in three or more studies. Most consistent results were found regarding ECMO duration and pH. However, evidence for risk factors was equivocal in the majority of studies, which is explained by the variability of populations studied, definitions of hemostatic complications, ECMO circuits, anticoagulation protocols, transfusion triggers and monitoring of anticoagulation. Five studies described alternative anticoagulants, including bivalirudin (n=3), argatroban (n=1) and FUT (n=1). Higher anti-factor Xa levels were associated with less clotting events in one of nine studies, investigating the association between tests and hemostatic complications. Two studies revealed an association between anti-factor Xa assay-based protocols and a decreased number of transfusions, bleedings and need for circuit change. Conclusion: Studies regarding risk factors showed conflicting results and a few retrospective studies reported the use of new anticoagulants and data on coagulation tests in relation to hemostatic complications. To decrease hemostatic complications in ECMO children, prospective multicenter studies are needed with clear bleeding and thrombotic definitions, and the best possible standardization of ECMO circuits used, anticoagulation protocols, and transfusion triggers.